Digital technologies, learning and school: practices and perceptions of young children (under 8) and their parents - Brito, Rita (2021)
This article explores the practices and perceptions of young children (under 8 years old) and their families about the use of digital technologies at school and their potential for learning, as well as the articulation between formal learning at school and informal learning at home. Data was collected through activities with children and their families, and then we used qualitative content analysis to explore them. The results show that the use of digital technologies at school is more common in Primary, being rare in Preschool. However, the pedagogical potential of devices like computers and tablets is underexplored both in schools and at home. Parents consider that children under 8 are too young for using digital tools in school work and believe they are not prepared to do so yet (although children are actually tech-savvy)